Pengaruh ekstrak biji persea americana terhadap kekasaran gigi tiruan resin akrilik heat cured (Laporan Penelitian) - Thesya Dhyah Anggraini; Nova Adiran (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Dental and oral health problem that is often experienced by people is tooth loss, therefore making denture is needed to replace missing teeth. This type of heat-cured acrylic resin is the most material used often for denture bases. Denture cleanser is necessary to avoid the growth of microorganisms. Persea Americana seed extract is one of the alternative natural ingredients that can be used as a denture cleanser because it inhibits the growth of microorganisms. The combination method is the most effective method for cleaning dentures and can affect the surface roughness of acrylic resin. Aim: To find out the effect of avocado seed extract (Persea Americana) on the surface roughness of acrylic resin denture heat cured. Method: This type of research is an experimental laboratory with pre-test and post-test group design. The study samples were 20x10x3 mm heat-cured acrylic resin with 20 samples. The samples were immersed in Persea Americana seed extract with 100% concentration for ten days and brushed for 45 minutes with a mass of 200g. Results: The results showed a significant change in the surface roughness of heat-cured acrylic resin after using a combination method cleanser with 100% concentration of Persea Americana seed extract (P<0,05). Conclusion: Persea Americana seed extract with 100% concentration was effect on surface roughness of heat-cured acrylic resin.